Mucin-1 expression in endometrium is higher in polycystic ovary syndrome than in normal women - Budihastuti, Uki Retno; Sulistyowati, Sri; Melinawati, Eriana; Marbun, Yohan Pamuji (Faculty of Medicine, Trisakti University, 2020)
BackgroundThe polycystic ovary syndrome (PCOS) is caused by endocrine system dysfunction in women. MUCIN-1 (MUC-1) expression is found in endometrial tissues, which leads to implantation process dysfunction because of imbalance of trophoblast adhesion process. This study was conducted to compare endometrial MUC-1 expression between PCOS and normal women considering all existing external variables.MethodsThis cross-sectional study was conducted in General Hospital Dr. Moewardi Surakarta. Endometrial samples were obtained from 30 infertile PCOS women based on Rotterdam criteria, and 30 normal women. Life style and reproductive data such as age, menstrual problems, menstrual cycle, age at menarche, and BMI were collected. Subjects underwent endometrial biopsy in luteinizing hormone (LH) secretion phase LH + 5 days to LH + 10 days for immunohistochemistry (IHC) of MUC-1 expression. An independent-t and multiple linear regression test were used to analyze the data at significance level of p<0.05. ResultsMean MUC-1 expression in the PCOS endometrium (49.66 Â± 47.79) was significantly higher than in normal women (7.66 Â± 14.55) (p=0.03). Multivariate linear regression model of life style and reproductive variables with MUC-1 showed that PCOS (b=29.54; 95% CI 9.57-49.49; p=0.004) and BMI (b= 29.99; 95% CI 5.91-54.07; p=0.001) significantly increase MUC-1 expression. PCOS (Beta=0.37) was more important than BMI (Beta=0.30) in increasing the MUC-1 expression. ConclusionExpression of MUC-1 levels in the PCOS endometrium was higher than in normal women. This suggests that MUC-1 contributes to the unexplained reproductive failure in PCOS.